DIRASAH TAHLILIYYAH AL-BINA’IYYAH WAS SIMA’IYYAH AN AD-DHOLAM LINAJIB MAHFUDH - Ihsanudin, Ihsanudin (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2018)
This study is aimed at examining az-Zalam short story by Najib Mahfudz because there are many language symbols that must be revealed to get meaning holistically. This research uses Robert Stanton's structural theory and C. Sanders Pierce's semiotic theory. This research involves the study of literature and employs a qualitative design by using descriptive analytical method. Based on the triadic concept of Pierce, Representament-object-intrepetant (ROI) the researcher gets the semiotic meaning of az-Zalam short story resulted from analyzing the symbols of the characters and the background of the story.